(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Shatavari, Asparagus racemosus is one of the most important herbal drugs used by Ayurvedic Vaidyas since ancient days. The drug is having wide range of therapeutic activity and mentioned as a Rasayan by ancient Ayurvedic texts. The main part used by Ayurvedic doctors is a root. It is mentioned as a tonic and having lactogenic function. Shatavari has also been successfully used by several Ayurvedic practitioners for Nervine disorders, Acid peptic diseases, certain infectious diseases and as a immunomodulant. Main use of this drug is in female disorders specially as a galactagogue and several menstrual disorders. Scientific fraternity is working on this drug at multidimensional level to prove this drug as a potent medicinal drug in multiple disorders. Various scientific studies are proved that this drug worked as a potent antitussive, antineoplastic, galactologue, antidiarroheal, and as immunomodulant. The main focus of this article is to review the scientific studies done on A.racemsosus mainly on its phytochemistry, pharmacology, therapeutic uses mentioned in both modern sciences as well as in ancient Ayurvedic texts. Additional attempt is made to find the clinical studies done on A.racemosus. The present review article includes the detailed scientific exploration of root extract of A.racemsosus in systematic way so that it can highlight future research prospects of this famous and commercially useful drug.